ARTIFICIAL INTELLIGENCE AND TEACHING METHODS - Ruziyeva Gulnoza Sherzodovna (Bright Mind Publishing, 2026)
Artificial intelligence (AI) is becoming an increasingly important tool in modern education, transforming traditional teaching methods and enhancing the learning process. This article examines the integration of AI into various aspects of education, including lesson planning, personalized learning, student assessment, and classroom management. AI technologies such as intelligent tutoring systems, adaptive learning platforms, virtual assistants, and educational data analytics help teachers better understand students’ needs, monitor progress, and provide targeted support. These technologies can also automate repetitive tasks, allowing educators to focus more on interactive and creative teaching methods. The article also discusses how AI contributes to personalized learning, where lessons and exercises are adapted to individual student abilities, learning styles, and pace. By analyzing data collected from students’ activities, AI systems can recommend suitable learning resources, identify knowledge gaps, and provide immediate feedback, thus improving overall learning outcomes. Furthermore, AI can enhance collaboration in the classroom, support remote learning, and promote innovative educational approaches, such as gamification and virtual reality experiences.
Keywords: Artificial Intelligence, Teaching Methods, Education, Personalized Learning, Intelligent Tutoring Systems, Lesson Planning, Student Assessment, Classroom Management, Educational Technology, Learning Outcomes, Adaptive Learning, Future Trends.